2006
DOI: 10.1021/es061528s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Isotope Exchange Methodology to Determine the Sorption Coefficient and Isotopically Exchangeable Concentration of Selenium in Soils and Sediments

Abstract: Isotope exchange methodology is invaluable to determine the solution-solid-phase distribution (Kd) and isotopically exchangeable concentration (Evalue) of elements in soils and sediments. This work examined the use of species-specific stable isotope exchange techniques to determine the Kd and E value of selenium (Se), as selenite (SeO3) and selenate (SeO4), in nine soils and sediments varying in concentration and source of Se. High-performance liquid chromatography-inductively coupled plasma-mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Finally, the compartment into which the tracer is added must behave homogenously in terms of exchange properties. In this case, the assumption made is that all chromate ions from the soil solution have the same behavior in terms of isotopic exchange properties (Collins et al 2006;Hamon et al 2004). According to the Cr Eh-pH diagram and the pH range of soils, HCrO 4 − represents 70 to 95% and CrO 4 2− 5 to 30% of the stable forms of Cr(VI) which can be present (Kotas and Stasicka 2000) and were defined hereafter as Cr(VI).…”
Section: Isotopic Exchange Kineticsmentioning
confidence: 99%
“…Finally, the compartment into which the tracer is added must behave homogenously in terms of exchange properties. In this case, the assumption made is that all chromate ions from the soil solution have the same behavior in terms of isotopic exchange properties (Collins et al 2006;Hamon et al 2004). According to the Cr Eh-pH diagram and the pH range of soils, HCrO 4 − represents 70 to 95% and CrO 4 2− 5 to 30% of the stable forms of Cr(VI) which can be present (Kotas and Stasicka 2000) and were defined hereafter as Cr(VI).…”
Section: Isotopic Exchange Kineticsmentioning
confidence: 99%
“…But labile pool of HMs is now widely measured using stable isotope technique because stable isotope techniques have several advantages over those employing radioactive tracers, such as a non-radioactive environment for the operator, less disposal and waste restrictions (Sterckeman et al, 2009). In addition, the species-specific E values such as selenite and selenate in soils can be also measured with the stable isotope exchange technique (Collins et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In flooded soils, reduction of added soluble Se(IV) or Se(VI) occurs within weeks with >80% of the added Se being fixed into non‐labile pools (Premarathna et al , 2010). Oxidation of reduced Se species is slow in soils with <20% of Se(0) being oxidized to Se(VI) within 60 days (Collins et al , 2006; Premarathna et al , 2010). Tokunaga et al (1991) found that more than 55 days were required to oxidize half of the newly formed (biologically) colloidal Se(0) to Se(IV) in a contaminated sediment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these sequential fractionation methods do not provide information about the strength of binding of Se with soil surfaces which may change with changing redox conditions. Isotope dilution methods using enriched stable or radioactive Se isotopes have been used successfully to examine the partitioning and lability of both Se(IV) and Se(VI) species simultaneously in aerobic and anaerobic soils (Collins et al , 2006; Premarathna et al , 2010). The study explained in the present paper was undertaken with a closed reaction system to examine in a controlled environment the influence of redox processes on solution speciation, partitioning and lability of added Se(IV) and Se(VI).…”
Section: Introductionmentioning
confidence: 99%